Papel do sistema de secreção do tipo 4 e proteína BtpA de Brucella abortus no estabelecimento do processo inflamatório em modelo de implante de matriz sintética - Monique Ferreira Silva (2019)
Human brucellosis caused by bacteria of the genus Brucella spp. is considered a debilitating chronic zoonotic disease. Brucella abortus is a Gram-negative, intracellular, facultative bacterium, considered endemic in many countries, and it is responsible for bovine and human chronic infections. After Brucella spp. infection, the host immune response is activated, but several virulence factors contribute for bacterium evasion of the immune system and persistence in the host favoring the establishment of chronic infection. Although Brucella spp. induces an insidious inflammatory response, little is known about the influence of bacteria on the establishment of acute inflammation in vivo, particularly in the synthetic sponge model. Thus, the goal of this study was to evaluate the acute inflammatory process induced by B. abortus infection and the influence of the Type 4 Secretory System (T4SS) and BtpA protein in the inflammatory process at 7 and 14 days after implantation of synthetic matrix in mice. This is the first study of the inflammatory profile induced by B. abortus 2308 infection in the in vivo model of synthetic biomaterial. B. abortus 2308, B. abortus ΔbtpA were able to survive and replicate in this model while B. abortus ΔvirB2 was attenuated, confirming its inability to cause persistent infection in vivo. B. abortus 2308 and ΔbtpA were able to modulate the inflammatory response in sponge differently than ΔvirB2. We observed that B. abortus 2308 and ΔbtpA induced lower influx of inflammatory cells, production of inflammatory mediators and formation of fibrovascular tissue at 14 days post-implant compared to the control or ΔvirB2- infected groups. B. abortus 2308 has the ability to inhibit inflammation in vivo and T4SS, but not BtpA, influences the course of the acute inflammatory process in the synthetic matrix model.